Inovasi Perencanaan Dakwah dengan Teknologi yang Berorientasi pada Tantangan Etis dan Strategi Penyampaian Pesan Islam - Friska Bella Nopianti; Ahmad Faiq Al-Alawi; Suci Ramadhani (Pusat Riset dan Inovasi Nasional, 2025)
Technology-driven Islamic propagation (da’wah) has emerged as a transformative paradigm in disseminating religious teachings in the digital age. The rapid advancement of social media platforms and artificial intelligence (AI) tools has significantly expanded the reach and influence of preachers, enabling more personalized and interactive engagement with diverse audiences. This study aims to explore innovative strategies in planning digital da’wah and to examine the challenges that arise, including the proliferation of misinformation, regulatory constraints, and the rise of underqualified digital preachers. Employing a qualitative approach through literature review and critical analysis of prior studies, this research highlights the potential of integrating data analytics, AI-based personalization, and digital media to enhance the effectiveness of Islamic messaging. However, it also underscores the pressing need for ethical frameworks and regulatory compliance to safeguard the integrity of religious content. The findings advocate for a structured, research-informed approach to digital da’wah that aligns with Islamic ethical principles while remaining adaptive to contemporary technological trends. Such an approach is essential to ensure that technological innovations serve as tools for meaningful religious engagement rather than sources of distortion or misinterpretation